Sputum cytology in the diagnosis of pulmonary paracoccidioidomycosis - Iwama de Mattos, M. C F [UNESP]; Mendes, R. P. [UNESP]; Marcondes-Machado, J. [UNESP]; Meira, D. A. [UNESP]; Morceli, J. [UNESP]; Pereira, P. C M [UNESP]; Barraviera, B. [UNESP] (Springer Nature, 1991)
The presence of Paracoccidioides brasiliensis was determined in sputum samples from 50 patients with paracoccidioidomycosis using four different techniques: (a) cell-block preparations stained with silver methenamine, (b) direct microbiologie examination, (c) smears stained with Shorr, and (d) smears stained with silver methenamine. Overall, cell-block preparations and smears stained with silver methenamine proved to be the most sensitive techniques, followed by smears stained with Shorr and direct microbiologic examination in decreasing order of sensitivity. Sputum cytology tended to be less positive in patients with interstitial pulmonary lesions as determined by chest X-ray than in patients with alveolar lesions. In addition to its high sensitivity, cell-block preparation technique allows storage of blocks and slides for further studies. © 1991 Kluwer Academic Publishers.
Keywords: cytology; lung disease; Paracoccidioides braciliensis; adult; aged; comparative study; female; human; isolation and purification; lung mycosis; male; microbiology; Paracoccidioides; prediction and forecasting; South American blastomycosis; sputum; Adult; Aged; Comparative Study; Female; Human; Lung Diseases, Fungal; Male; Middle Age; Paracoccidioidomycosis; Predictive Value of Tests; Sputum